Do Good Working Conditions Make You Work Longer? Evidence on Retirement Decisions Using Linked Survey and Register Data - Petri Böckerman; Pekka Ilmakunnas (Institute of Labor Economics (IZA), 2017)
We analyze the potential role of adverse working conditions and management practices in the determination of employees' retirement behavior. Our data contain both comprehensive information regarding perceived job disamenities, job satisfaction, and intentions to retire from nationally representative cross-sectional surveys and information on employees' actual retirement decisions from longitudinal register data that can be linked to the surveys. Using a trivariate ordered probit model, we observe that job dissatisfaction arising from adverse working conditions is significantly related to intentions to retire, and this in turn is related to actual retirement during the follow-up period.
Keywords: J26; J28; J53; 330; working conditions; job satisfaction; retirement; new management practices